Nutrient Solution Selection Modulates Growth Patterns and Leaf Elemental Accumulation in Alfalfa (Medicago sativa) Grown - Jiaqing Li; Yingjian Zhu; Zhenwu Wei; Haowen Chen; Chuanjie Wang; Kai Cao; Xian Zhang (Agronomy)
While forage grasses in southern China exhibit yield and nutritional advantages, the impact of nutrient solutions on alfalfa (Medicago sativa BC4) growth and elemental accumulation remains understudied. We conducted a pot-based controlled substrate cultivation trial using a nitrogen-poor substrate to compare four treatments: MS, Hoagland, B5 nutrient solutions, and RO water (control). From the V1 to R1 stages, the plant height was monitored continuously, with leaf dimensions and soluble proteins (Bradford method) measured at R1. ICP-MS quantified macro elements (Na+, K+, and Mg2+) and microelements (Cu2+, Fe2+, Mn2+, and Zn2+). The growth rates followed the order: MS > Hoagland > RO water > B5. Both the MS and Hoagland solutions significantly increased the leaf length at the R1 stage (p < 0.001 vs control), with Hoagland showing the greatest leaf expansion. The soluble protein content decreased significantly in all groups (p < 0.05) except MS-treated plants. An elemental analysis revealed treatment-specific accumulation patterns, most notably 1.17-fold higher Fe and 1.48-fold higher Mn in the MS group versus control (p < 0.001). Magnesium levels showed no significant differences among treatments. These results demonstrate the MS nutrient solution’s superior efficacy in enhancing the alfalfa growth parameters (height and leaf size) while maintaining the soluble protein content and promoting Fe/Mn accumulation. The findings provide empirical evidence for optimizing alfalfa cultivation in a nitrogen-deficient soil-based mix substrate through nutrient solution selection.